Structural analysis of fibreglass reinforced bonded flexible pipe subjected to tension. (3rd October 2019) - Xu, Yuxin; Bai, Yong; Fang, Pan; Yuan, Shuai; Liu, Chang
ABSTRACT: Fibreglass reinforced flexible pipe (FGRFP) is regarded as a great alternative to bonded flexible pipes in the field of oil or gas transportation. FGRFP is compounded by high-strength fibreglass and thermoplastic material, which subjected to tension loading in the process of installation and operation. In this paper, the mechanical behaviour of FGRFP subjected to tension is investigated by experimental, theoretical and finite element methods (FEM). Previous related research has mainly focused on laminated-plate theory without considering material nonlinearity. However, not only can the analytical model adopted in this paper take material nonlinearity into consideration, but it can also evaluate the specific effects of each material. Full-scale laboratory tests were conducted and the relationship between axial loads and extensions of FGRFP acquired from the experiment is compared with that of theoretical and FE simulations. Good agreements demonstrate the accuracy and reliability of the analytical model and FEM. Then, detailed responses of the high-density polyethylene and fibreglass under pure tension are analysed. In addition, the parametric study on the structural response is conducted to provide a valuable reference for engineering practices. This work may provide an improved method for estimating structural response of composite pipes with helical reinforced layers.